A near-infrared and two-photon dual-mode fluorescent probe for the colorimetric monitoring of SO2in vitro and in vivo. Issue 14 (14th June 2019) - Kong, Xiuqi; Li, Min; Dong, Baoli; Zhang, Nan; Song, Wenhui; Lu, Yaru; Lin, Weiying
Abstract : A near-infrared and two-photon dual-mode fluorescentCY probe was developed for the colorimetric monitoring of SO2 in vitro and in vivo . Abstract : SO2 has been recently identified as an essential gas messenger followed by NO, CO and H2 S. However, abnormal concentrations of SO2 in our bodies can cause many diseases. Thus, the real-time monitoring of SO2 to well define the generation, physiological and pathological functions of SO2 is urgently needed. In this work, we developed a novel SO2 fluorescent probe on the basis of the conjugation of semi-cyanine and coumarin derivate dyes with superior features, such as near-infrared (NIR) and two-photon dual-mode monitoring, a large Stokes shift (175 nm), ultrafast response towards SO2 (within 10 s), high selectivity and photostability. Furthermore, this probe could sense SO2 by dual colorimetric and fluorescence means. In biological imaging, the probe was able to trace exogenous and endogenous SO2 in living cells, mitochondria, E. coli, zebrafish and mice under an NIR and two-photon dual-mode. These results demonstrated that the probe has strong potential for studying the physiological and pathological functions of SO2 in vitro and in vivo .